Wear and Grip Loss Evaluation of High Chromium Welding Deposits Applied on Sugar Cane Rolls1 - Diaz Millan, Sebastian (2015)
Wear on sugar cane rolls is an expensive maintenance problem for the sugar cane industry. Wear produces loss of sucrose extraction and loss of grip of the roll on the bagasse. This paper presents the evaluation of wear and loss of grip of hypoeutectic and hypereutectic high chromium welding deposits applied on ASTM A-36 steel and gray cast iron. A modified ASTM G-65 standard test was used. Wear was produced by the abrasive action of wet bagasse with three levels of mineral extraneous matter. Silica grains with sizes in the range of 0.212-0.300 mm (AFS 50/70) were used as mineral extraneous matter. Grip was evaluated by measuring the torque on the power transmission shaft that moves the specimens. Worn surfaces were characterized by using scanning electron microscopy. Wear was found to increase proportionally related to the mineral extraneous matter content. Geometric changes of the weld deposits related to wear caused grip loss. For low mineral extraneous matter level, wear resistance of carbon steel was greater than that of gray cast iron; whereas the opposite was found for high mineral extraneous matter level.